2023
DOI: 10.1007/s40725-023-00179-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Silvicultural Treatments and Forest Operations on Tree Species Biodiversity

Abstract: Purpose of Review Biodiversity is one of the most important features of forest ecosystems. One of the goals of Sustainable Forest Management is to reduce biodiversity disturbance, which can occur as a consequence of timber harvesting. The aim of this review was to define which silvicultural systems and forest operations can have an influence on forest tree biodiversity by summarising the findings of nearly 60 papers published in the last ten years (2013–2022). Recent Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…For 58 of 217 couple comparisons in the database, we did not obtain data about the dispersion measure. Thus, we assessed the relationship between the standard deviation and the average values presented in our database to fulfil this gap (Latterini, Dyderski, et al, 2023; Pigott, 1994; Wiebe et al, 2006). Due to non‐linearity, we used a power model (Equation 1), after a log‐transformation to better handle a wide range of values in our dataset (Equation 2): SD=a·normalMnormalb, logSD=a+b·lognormalM, where SD—standard deviation, M—mean, a and b—model parameters.…”
Section: Methodsmentioning
confidence: 99%
“…For 58 of 217 couple comparisons in the database, we did not obtain data about the dispersion measure. Thus, we assessed the relationship between the standard deviation and the average values presented in our database to fulfil this gap (Latterini, Dyderski, et al, 2023; Pigott, 1994; Wiebe et al, 2006). Due to non‐linearity, we used a power model (Equation 1), after a log‐transformation to better handle a wide range of values in our dataset (Equation 2): SD=a·normalMnormalb, logSD=a+b·lognormalM, where SD—standard deviation, M—mean, a and b—model parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Another form of damage in the forest is injury to the remaining trees in the stand and damage to young seedlings, which occur in selective cutting and shelterwood systems (Picchio et al, 2020b). The mechanization level in some cases can influence the damage magnitude species diversity but more other variables participate (Latterini et al, 2023). Some researchers have shown that mechanized harvesting damage on each of the vegetative groups of seedlings, juveniles, and saplings is more than semi-mechanized harvesting damages (Hosseini et al, 2002;Naghdi et al, 2009), however, in some other studies was showed the contrary (Stańczykiewicz et al, 2015) or founded like only matching machine/equipment type, size and deployment to stand and site conditions damage to regeneration can be limited (Picchio et al, 2020b).…”
Section: Harvesting Damage On Residual Stand and Regenerationmentioning
confidence: 99%
“…For example, forest soils reserve >40% of the total organic carbon (C) in terrestrial ecosystems and are thus important regulators of CO 2 on a global scale (Jourgholami, Fathi, & Labelle, 2020; Jourgholami, Khajavi, & Labelle, 2020; Wei et al, 2014). Timber harvesting normally causes a decrease in soil carbon stocks (DeArmond et al, 2021; Latterini et al, 2023; Mayer et al, 2020). In addition, mechanized harvesting and logs transported by ground‐based skidding machines can disturb forest soils and decrease periodically the productivity of the forest (Horn et al, 2004; Labelle et al, 2022; Venanzi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%